PERTANGGUNGJAWABAN PERDATA DAN ADMINISTRATIF TENAGA MEDIS DALAM KASUS MALAPRAKTIK - Gunawan Widjaja (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study discusses the forms and legal basis of civil and administrative liability of medical personnel in cases of malpractice in Indonesia using a literature review method. The findings reveal that civil liability is based on the principle of unlawful acts as stipulated in the Civil Code and the Health Law, which require medical personnel or hospitals to compensate patients if negligence causing harm is proven. Meanwhile, administrative liability arises when medical personnel violate administrative regulations or professional discipline, with sanctions ranging from warnings to revocation of practice licences, imposed through an examination mechanism by the Indonesian Medical Disciplinary Council (MKDKI). This study underscores the importance of harmonising regulations and enhancing transparency in dispute resolution mechanisms to ensure optimal legal protection for both patients and medical personnel.